On Machiavelli’s Conception of the Good Prince - Simian, Rafael (Pensamiento. Revista de Investigación e Información Filosófica, 2021)
Traditionally, Machiavelli’s Prince has been read as defending a new ethico-political ideal, thus aiming to invalidate and replace those of Cicero and of Christianity. However, Cassirer, Viroli, and Berlin have argued, each in their own way, that this is not true. The essay presents these interpreters’ readings and highlights their main points. Then it examines Machiavelli’s texts to see whether those points are correct. The textual analysis leads to the conclusion that the traditional reading is plausible, whereas the other three are unconvincing. Stress is made on the fact that Machiavelli’s ethico-political ideal in The Prince involves serious restrictions: First, it is not an ideal valid for everybody; and second, it is valid only under certain political circumstances which escape our control and make it necessary for the life and prosperity of the community.
Keywords: Niccolò Machiavelli; The Prince; Ernst Cassirer; Maurizio Viroli; Isaiah Berlin; ethics